1990
DOI: 10.1109/19.57233
|View full text |Cite
|
Sign up to set email alerts
|

Neural network signal understanding for instrumentation

Abstract: Abstract-This paper reports on the use of neural signal interpretation theory and techniques for the purpose of classifying the shapes of a set of instrumentation signals, in order to calibrate devices, diagnose anomalies, generate tuning/settings, and interpret the measurement results. Neural signal understanding research is surveyed, and the selected implementation is described with its performance in terms of correct classification rates and robustness to noise. Formal results on neural net training time an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…(1) 7 is a sensitivity parameter that depends on the physical geometry and material properties of the CPS.…”
Section: -Nmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) 7 is a sensitivity parameter that depends on the physical geometry and material properties of the CPS.…”
Section: -Nmentioning
confidence: 99%
“…Some of the early applications of NN in instrumentation and measurement can be found in [7]- [11]. Application of NNs with superior performance for nonlinearity estimation in pressure sensor [12], compensation for environmental dependency and nonlinearities of sensor characteristics in pressure sensors [13]- [14] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The wide applicability of NNs stems from their flexibility and ability to model non-linear systems without prior knowledge of an empirical model. This gives ANNs an advantage over traditional fitting methods for instrumentation and measurement (Pau and Johansen 1990) and industrial processes (Haykin 1998). The availability of an input-output ANN model for a complex process allows the prediction of the system behavior.…”
Section: Introductionmentioning
confidence: 99%
“…These networks are endowed with certain unique characteristics such as the capability of universal approximation, generalization, and fault tolerance. Because of these characteristics, there have been numerous successful applications of NNs in various fields of science, engineering, and industry [8,9,10]. It has been shown that the NN-based approximations to measurement data perform better than those of the classical methods of data interpolation and least mean square regression [11].…”
Section: Introductionmentioning
confidence: 99%